Diseño y aplicación de talleres sobre violencia escolar para mejorar la convivencia institucional y familiar en los estudiantes de los séptimos años de educación general básica, de la Escuela Isidro Ayora, cantón Latacunga, durante el año lectivo 2012 – 2013 - Hervas Freire, Pablo Andrés (2015)
In ECUADOR outbursts of violence are a normal feature in childhood but some children persist in their aggressive conduct and his inability to control their temper, such children make their parents and teachers enconunter serious problems when control them so ofthen these children are destined to frustrations that make the child feel rejected by their peers when they can not prevent the conduct violent. Necessarily have to ask first, which are the children do at home and the school students are doing exactly, referring to their conduct, if the aanswer is vague and somewhat confusing to be impossible to clearly identify the problem, so it is pertinent to ask what the reaction of the child or student when this is teased and aggression at home and the school. If we set up workshops to change the conduct violent that keep certain students within the FAMILY CIRCLE at first, and the within SCHOLAR SITUATION, we don´t that the changes will not occur from one day to another, but patience is need by specially many perseverance if you want to resolve the problem from homes after that, applying the same solution in educational institutions, knowing clearly the above modification of conduct violent went different phases that go from clear definition of the problem until the evaluation of the results. To carrid valid actions in controlling conduct violent need a model or theory to follow and this, in our case will be theory usually social learning when a child emits conduct violent because it reacts to conflict, the conflict can be of problems of social relationships with other children or older in fact satisfy the desires of coexistence of the himself.